2019
DOI: 10.1186/s40163-019-0100-5
|View full text |Cite
|
Sign up to set email alerts
|

Crime concentration at micro-places in Latin America

Abstract: Research on crime concentration at micro-places has had a very western-industrialised focus. In this paper we provide results on crime concentration for 42 cities in Latin America. The results suggest that crime is concentrated at higher levels in Latin American cities than in western-industrialised contexts. Reasons for this do not appear to be related to population size, average street length, numbers of crimes or crime rates. The results offer an indication of the crime reduction opportunities that could co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 9 publications
4
8
0
1
Order By: Relevance
“…Table 1 shows that the levels of crime concentration across street segments in Florianópolis and Joinville were high and similar: the proportion of street segments that accounted for 50% of crimes was 1.1% and 1.6%, respectively. These results are consistent with findings on the high levels of geographic crime concentration of robberies in other Latin American settings [14] and that the implementation of a hot spot policing program in each city would be worthwhile.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Table 1 shows that the levels of crime concentration across street segments in Florianópolis and Joinville were high and similar: the proportion of street segments that accounted for 50% of crimes was 1.1% and 1.6%, respectively. These results are consistent with findings on the high levels of geographic crime concentration of robberies in other Latin American settings [14] and that the implementation of a hot spot policing program in each city would be worthwhile.…”
Section: Resultssupporting
confidence: 90%
“…Evidence shows that police patrols that are not directed to the areas in most need have limited impact in decreasing crime [11,12] whereas targeting the deployment of police patrols to crime hot spots, i.e., hot spot policing, can significantly decrease crime [1,13]. Crime hot spots are areas where crime is observed to highly concentrate, with this patterning observation being consistent in a range of international settings [14][15][16] (and at different geographic scales of analysis [17]). For example, in New York City, Vancouver, and Rio de Janeiro, studies have shown that less than 5% of places accounted for 50% of crimes [18][19][20].…”
Section: Hot Spot Policing Geographic Concentration Of Crime and The Creation Of Hot Spot Patrol Routesmentioning
confidence: 97%
“…This proved to be the case with no more than 20 of Brazil's 5570 cities (0.36%) being responsible for at least a quarter of all homicides in any year. This level of spatial concentration is comparable to the patterns of homicide concentration observed at micro-places (i.e., street segments) within cities across Latin America [58] and suggests a consistency in the spatial concentration of crime for geographic units across geographic scales. Similar to street segments, cities vary in size.…”
Section: Discussionsupporting
confidence: 65%
“…The study of the geography of crime has increasingly focused on the micro-place (such as the street segment) as the geographic unit of analysis. A consistent finding from numerous studies on micro-place patterns of crime is that a small number of places are responsible for a large proportion of crime [16,[57][58][59]. Many of these studies have applied the bandwidths suggested by Weisburd [16] for comparing between settings and different crime types.…”
Section: Spatial Concentration and Emerging Problem Areasmentioning
confidence: 98%
“…In connection with these questions, there is an increasing research interest in the law of crime concentration, which states that "for a defined measure of crime at a specific microgeographic unit, the concentration of crime will fall within a narrow bandwidth of percentages for a defined cumulative proportion of crime" (Weisburd, 2015). Hence, whereas the law of crime concentration has been verified for multiple cities and regions in the last few years (Amemiya & Ohyama, 2019;Chainey et al, 2019;Umar, Johnson, & Cheshire, 2020), there seems to be greater uncertainty around the extent to which crime hotspots corresponding to different crime types tend to overlap spatially.…”
Section: Introductionmentioning
confidence: 99%